Paid work beyond pension age comparative perspectives - Scherger, Simone (Palgrave Macmillan, 2015)
In many countries, the number of people working beyond pension age is increasing. This volume investigates this trend in seven different countries, examining the contexts of this development and the consequences of the shifting relationship between work and retirement